Cuadro de mando integral como herramienta para el control de gestión en la comercializadora de productos lácteos LACYCOM CIA LTDA. del cantón-Portoviejo - Ormaza Franco, Pablo Alexi (2019)
The summary of this work was to develop a balanced scorecard in the marketer of dairy products Lacycom Cia Ltda, located in Portoviejo canton. The procedure of this research consisted of three phases in the first methodological, met the internal dynamics of the trading company, through interviews and surveys applied to the manager and owner of the same on the basis of the perspectives of the balanced scorecard. In the second phase, the management indicators for measuring the strategic objectives were determined, the SWOT matrix in which identified the strategies and identified strategic objectives, then a group of experts selected the most suitable indicators for evaluation. In the third phase, structuring elements of the strategic perspectives that are linked to the Scorecard were started; in addition to the design of the strategic map of the marketer, subsequently developed the design of the scorecard composed of strategic objectives, indicator, operational definition, meta, variations of compliance and responsible for its implementation. As a result, it was observed that the internal dynamics of the marketer Lacycom Cia Ltda, the Internal Process Perspective with 85% met at an optimum level, training and growth with 82% and client with 80 %, while the financial met at an average level with 59%.